Factores maternos-ambientales y malformaciones congénitas del sistema digestivo en recién nacidos - Bazán Luján, Flor Angel (2019)
This descriptive, explanatory, cross-sectional research study was developed with the aim of identifying maternal-environmental factors and congenital malformations of the digestive system of newborns in the Hospital Victor Lazarte Echegaray in 2018. The sample universe consisted of 20 newborns diagnosed with congenital malformation of the digestive system. For the data collection the medical history was used, data was taken of the newborn and the mother, through interview. The information obtained was tabulated and organized into single and double input tables, then processed using the SPSS system, version 23. The results were: 80% of the mothers of newborns with malformations of the digestive system, were between 35 years of age, 65% with higher education and 55% consumed the folic acid indicated during their pregnancy. In addition 65% received full vaccination, 70% reported having consumed alcohol, 75% consumed drugs and only 20% were exposed to herbicides and pesticides.